ANALISIS STRATEGI PENGEMBANGAN WISATA DI LUBUK LANGKAP GUNA MENINGKATKAN KUNJUNGAN WISATA AIR TAWAR KECAMATAN AIR NIPIS KABUPATEN BENGKULU SELATAN - Putri, Rana Marita (Jurnal Entrepreneur dan Manajemen Sains (JEMS), 2024)
The objective of this study is to examine the strategy of tourism development in the Lubuk Langkap in order to increase freshwater tourism visits. This type of research uses qualitative descriptive in field research. The informants in the study are the Tourism Department of Bengkulu District South, the Village Government and Visitors. The findings of this study show that internal strengths and weaknesses have a total score of 3.33, approaching the point position (3.0-4.0) in field II, the green color identifies that has an internal factor that grows. In addition, external opportunities and threats have a overall score of 2.59 in field IV, the blue color identifies that external factors are growing. Recommendation to the Tourism Department of Bengkulu District South and the Village Government to make more efforts to develop the tourism area, manage and promote it so that it is better known to the widespread tourists or tourist visitors. Keywords: Development strategy and increasing visits